2022
DOI: 10.3390/ma15217859
|View full text |Cite
|
Sign up to set email alerts
|

Computational Probing of Tin-Based Lead-Free Perovskite Solar Cells: Effects of Absorber Parameters and Various Electron Transport Layer Materials on Device Performance

Abstract: Tin-based perovskite solar cells have gained global research attention due to the lead toxicity and health risk associated with its lead-based analog. The promising opto-electrical properties of the Tin-based perovskite have attracted researchers to work on developing Tin-based perovskite solar cells with higher efficiencies comparable to lead-based analogs. Tin-based perovskites outperform lead-based ones in areas such as optimal band gap and carrier mobility. A detailed understanding of the effects of each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…From Figure 2 c it is observed that the PCE increases with the higher metal work function of the Ag paste up to a certain work function value (5 eV). The reason behind such an increment in the work function value is the decrement of the height of the carrier barrier, and as a result, the metal contact becomes ohmic in nature [ 8 ]. Thus, open circuit voltages also increase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From Figure 2 c it is observed that the PCE increases with the higher metal work function of the Ag paste up to a certain work function value (5 eV). The reason behind such an increment in the work function value is the decrement of the height of the carrier barrier, and as a result, the metal contact becomes ohmic in nature [ 8 ]. Thus, open circuit voltages also increase.…”
Section: Resultsmentioning
confidence: 99%
“…As per the observations, the diffusion length increases with the open circuit voltage (V OC ) for all the seven absorbing materials except for Cs 2 TiI 5 Br 1 and Cs 2 TiI 6 , where the diffusion length decreases after 0.6 V. The concentrations of electrons and holes are enhanced with the voltage which leads to an increment in diffusion length. The diffusion length of the electrons and holes should be higher than the absorbing layer thickness [ 8 ], since Cs 2 TiBr 6 , Cs 2 TiI 1 Br 5 and Cs 2 TiI 6 absorbing materials have a band gap above 1.50 eV which requires large energy to excite an electron in the conduction band. Thus, such materials operate in a higher temperature which can burn the device after a certain temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, the work had a conversion efciency of 23.76% [17]. For the proposed (Zn 2 SnO 4 / CH 3 NH 3 SnI 3 /Spiro-MeOTAD) structure, the obtained conversion efciency in 2021 is 24.73% [18]. In 2017, it had a conversion efciency of 24.82%, J SC of 25.67 mA/cm 2 , FF of 78.14% and V OC of 1.0413 V [19].…”
Section: Introductionmentioning
confidence: 92%
“…Drift-diffusion modelling can be utilised for this purpose. 21–24 Material properties such as band structure, Eigen states, and the electron-density profile can be analysed by Device Studio software with a “nanodcal” package. Addition of Fe and Ni to DMACF can improve the bandgap of the material (an essential factor for solar-cell efficiency).…”
Section: Introductionmentioning
confidence: 99%